EVOLUSI, SPESIASI, DAN HIBRIDISASI PADA BEBERAPA ANGGOTA SAPINDACEAE - Djuita, Nina Ratna (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2012)
Evolution in Sapindaceae have been running for a long time, as evidenced by the fossil of Sapindopsis encountered in the mid Cretaceous. Based on its characteristics, the genus is thought to live in stressful environments. Sapindaceae has the habitus of shrubs, trees, climbers, and the vine. Speciation in Sapindaceae can be found in genus Acor, while members of Sapindaceae which had hybridization can be found in genus AesculusEvolution in Sapindaceae have been running for a long time, as evidencedby the fossil of Sapindopsis encountered in the mid Cretaceous. Based on its characteristics, the genus is thought to live in stressful environments. Sapindaceae has the habitusof shrubs, trees, climbers, and the vine. Speciation in Sapindaceae can be found in genusAcer, while members of Sapindaceae which had hybridization can be found in genus Aesculus.